The answer is B. I got this answer by figuring out how to measure the linear equation by breaking it down.
(5+4+6-2)×2×2-1
(9-4)×2×2-1
5×2×2--1
10×2-1
20-1
19
Step-by-step explanation:
7=4y-13
7+13=4y
20/4=y
5=y
Answer:
A
Step-by-step explanation:
Have a good day. ;-)
Answer:
Multiply by ∛2 and translate the graph to left by 4 units.
Step-by-step explanation:
The initial function given is:
y = -∛(x - 4)
The transformed function is:
y = -∛(2x - 4)
Consider the initial function.
y = -∛(x - 4)
(Represented by Black line in the graph)
Multiply the function by ∛2. The function becomes:
y = -∛(x - 4) × ∛2
y = -∛(2)(x-4)
y = -∛(2x-8)
(Represented by Red line in the graph represents this function)
Translate the graph 4 units to the left by adding 4 to the x component:
y = -∛(2x-8+4)
y= -∛(2x - 4)
(Represented by Blue line in the graph)